Metode SAS Berbasis Gambar Untuk Meningkatkan Kemampuan Membaca Permulaan Anak Tunagrahita Ringan Di SLB Bhakti Luhur Malang - Klemensia Nini; Maria Oktaviana Lika (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2024)
This study aims to evaluate the effectiveness of the image-based Synthetic Analytical Structure Method (SAS) in improving early reading skills in children with mild intellectual disabilities at SLB Bhakti Luhur Malang. The application of the SAS method consists of three stages, namely the introduction of complete sentences accompanied by images, analysis of sentence elements into words, syllables, and letters, and re-synthesis of these elements into complete sentences. The method used is the single subject experiment method (Single Subject Research) with an A-B-A design. This method was chosen to evaluate the effectiveness of the image-based Synthetic Analytical Structure Method (SAS) in improving early reading skills in children with mild intellectual disabilities at SLB Bhakti Luhur Malang. At the baseline stage 1 (A1) reading ability is measured without intervention, while the intervention stage (B) the SAS method is applied which combines sentence recognition with images and synthetic analysis of sentence elements. The results showed an increase in the subject's reading ability from 29% from the baseline phase (A1) to 62% in the intervention phase (B), and reached 84% in baseline phase 2 (A2). These results indicate that this approach not only improves reading comprehension, but also encourages student involvement in more active and interesting learning activities. Despite significant improvements, children with intellectual disabilities still need additional guidance in combining letters and words from more complex sentence variations. The results and findings of this study provide opportunities for further research to continue to improve the quality of education for children with special needs and maximize their potential in reading. The results of this study make an important contribution to the development of more effective and creative teaching methods for children with special needs. This research opens up opportunities for further studies to address the challenges of reading instruction in the group of children with intellectual disabilities.